The primary stability of ultrashort residual proximal femur fixed with triangular fixation stem prosthesis: a comparative biomechanical study based on sawbones models - Hou, Ziwei; Zheng, Kai; Xu, Ming; Yu, Xiuchun (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Tumor resection near the proximal end of the femur and revision surgery of the distal femoral prosthesis may result in a very short bone segment remaining at the proximal end of the femur, known as ultrashort residual proximal femur (URPF). In this study, we propose a triangular fixation stem (TFS) prosthesis to improve the fixation of URPF. The aim of this research is to investigate the biomechanical properties of the TFS prosthesis and compare it with the conventional stem (CS) prosthesis through in vitro biomechanical experiments, providing preliminary biomechanical evidence for prosthetic fixation of URPF. Methods: A biomechanical study was conducted using Sawbones to explore initial stability. Twelve Sawbones were used to create a bone defect model, and prostheses were designed and fabricated to emulate TFS fixation and CS fixation structures. Axial compression and horizontal torsion experiments were performed on the fixed models using a mechanical testing machine, recording maximum displacement, maximum torque, and femoral strain conditions. Results: Under an axial compressive load of 2800 N, the overall displacement of the TFS group was 3.33 ± 0.58 mm, which was significantly smaller than that of the CS group (4.03 ± 0.32mm, P = 0.029). The femoral samples of the TFS group demonstrated that the strain value alterations at the medial points 2, 3, 5, 6 and the lateral point 10 were conspicuously smaller than those of the conventional stem group (P < 0.05). Under torsional loads at levels of 1°, 3°, and 5°, the torques of the TFS group were 3.86 ± 0.69 Nm, 3.90 ± 1.26 Nm, and 4.39 ± 1.67 Nm respectively, all of which were significantly greater than those of the CS group (1.82 ± 0.82 Nm, P < 0.001; 2.05 ± 0.89 Nm, P = 0.016; 1.96 ± 0.50 Nm, P = 0.015 respectively).The TFS prosthesis improves fixation strength and reduces stress on the femur's proximal surface. Compared to CS fixation, it offers better resistance to compression and rotation, as well as improved initial stability.